2007
DOI: 10.1007/s10577-007-1175-5
|View full text |Cite
|
Sign up to set email alerts
|

Tpp1/Acd maintains genomic stability through a complex role in telomere protection

Abstract: Telomeres serve to protect the ends of chromosomes, and failure to maintain telomeres can lead to dramatic genomic instability. Human TPP1 was identified as a protein which interacts with components of a telomere cap complex, but does not directly bind to telomeric DNA. While biochemical interactions indicate a function in telomere biology, much remains to be learned regarding the roles of TPP1 in vivo. We previously reported the positional cloning of the gene responsible for the adrenocortical dysplasia (acd)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
5
29
1
Order By: Relevance
“…Both outcomes cause premature termination of translation and a truncated protein lacking all functional domains. Homozygosity for acd decreases the expression of WT transcripts to approximately 2% of normal levels, consistent with a profoundly hypomorphic phenotype (35). Analysis of the fetal livers from E13.5 acd-mutant mice revealed a mild decrease in fetal liver cellularity compared with that in the control littermates ( Figure 1B).…”
Section: Acd Deficiency Results In Cell Cycle Arrest and Impaired Funmentioning
confidence: 61%
See 1 more Smart Citation
“…Both outcomes cause premature termination of translation and a truncated protein lacking all functional domains. Homozygosity for acd decreases the expression of WT transcripts to approximately 2% of normal levels, consistent with a profoundly hypomorphic phenotype (35). Analysis of the fetal livers from E13.5 acd-mutant mice revealed a mild decrease in fetal liver cellularity compared with that in the control littermates ( Figure 1B).…”
Section: Acd Deficiency Results In Cell Cycle Arrest and Impaired Funmentioning
confidence: 61%
“…This allele was originally described to cause adrenocortical dysplasia and was thus named acd (30). It is characterized by a G to A transition within the third intron ( Figure 1A), resulting in aberrant splicing and either a 7-bp insertion after exon 3 or inclusion of the third intron in the mRNA (30,35). Both outcomes cause premature termination of translation and a truncated protein lacking all functional domains.…”
Section: Acd Deficiency Results In Cell Cycle Arrest and Impaired Funmentioning
confidence: 99%
“…It is located on 16q22.1, a locus previously shown to be deleted in human breast tumors (Roylance et al 1999(Roylance et al , 2006. The protein plays a role in telomere protection (Else et al 2007). ELAC1 and CDH20 are both localized to 18q.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that TPP1 plays an essential organizing function in shelterin, predicting that its deletion would affect TRF1 and TRF2 (25). Furthermore, cytogenetic data on cells from the adrenocortical dysplasia (Acd) mouse strain, which carries a hypomorphic mutation for TPP1 (14), revealed complex chromosomal rearrangements in addition to telomere fusions, leading to the suggestion that TPP1 might have additional telomeric or nontelomeric functions (9).…”
mentioning
confidence: 99%